A persistência da book-tax differences nas informações contábeis das companhias abertas de países da América Latina - Cardoso, Tatianne Aparecida de Oliveira (2017)
This paper aims to analyze if the adoption of IFRS has impacted on book-tax differences (BTD) persistence and it types on Latin American countries. BTD persistence can be used to investigate accounting and tax profit persistence simultaneously. When it is related to BTD persistence with IFRS adoption, it seeks to analyze if the accounting choices have not affected the accounting information quality. The research sample is composed by 654 open companies from six Latin American countries (Argentina, Brazil, Chile, Mexico, Peru and Venezuela) which converged to IFRS from 2001 to 2015, and have available data on Thompson’s database. The presented data was estimated using GMM - Generalized Method of Moments, and it persistence was tested through AR - One Period Autoregressive process (1). This work has identified that, after IFRS utilization, BTD persistence has presented a significant and negative coefficient, indicating that there has been a decline in all BTD persistence types. After IFRS adoption, the reason of the quality decline can be motivated by the accounting choices, where the managers, can make choices, which can cause an oscillation in reported profit, making it difficult to predict future profits, affecting the BTD persistence.